2012
DOI: 10.1007/s00380-012-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of morphological and functional adaptations of the heart in highly trained triathletes and long-distance runners using cardiac magnetic resonance imaging

Abstract: "Athlete's heart" is characterized by an increase in ventricular chamber sizes and myocardial mass (MM), and is mainly observed in endurance athletes. At present, it remains unclear whether cardiac adaptations in long-distance runners differ from those in triathletes. Twenty male triathletes (mean age 38.7 ± 6.2 years) and 20 male marathon runners (mean age 44.1 ± 7.9) underwent cardiac magnetic resonance imaging to calculate left and right ventricular end-diastolic volume (EDV), end-systolic volume (ESV), str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Our finding of a significantly greater RV than LV volume in the athlete group did not apply to the [23][24][25][26] Interestingly, our morphological finding of mild angular deviated bulging at the basal to midventricular part of the RV free wall in our athlete's cohort may signify that the RV dilation induced by long-term endurance training primarily involves the RV main body. A review by the study group of LaGerche 27 dealing with the athlete's heart also describes a bulging of the RV free wall in endurance athletes.…”
Section: Morphological Parameterscontrasting
confidence: 60%
See 2 more Smart Citations
“…Our finding of a significantly greater RV than LV volume in the athlete group did not apply to the [23][24][25][26] Interestingly, our morphological finding of mild angular deviated bulging at the basal to midventricular part of the RV free wall in our athlete's cohort may signify that the RV dilation induced by long-term endurance training primarily involves the RV main body. A review by the study group of LaGerche 27 dealing with the athlete's heart also describes a bulging of the RV free wall in endurance athletes.…”
Section: Morphological Parameterscontrasting
confidence: 60%
“…Several other studies conducted with cardiac MRI among athletes did not detect any LE, whereas they confirmed chronic remodeling of both the LV and RV. 5,26,33 Our results demonstrate that, in the vast majority of elite endurance athletes with a long-term intensive training history, no signs of myocardial damage could be detected, thus indicating that even long-term intensive endurance training does not seem to induce myocardial necrosis or fibrosis at least in welltrained and exercise-adapted athletes. This finding is supported by the fact that none of the athletes had shown any arrhythmias during the cardiopulmonary exercise test up to exhaustion nor described any symptoms related to malignant arrhythmias in the past.…”
Section: Late Enhancementmentioning
confidence: 62%
See 1 more Smart Citation
“…11 In contrast, Franzen et al demonstrated that LGE was absent in 20 men triathletes and 20 men middle-aged marathon runners. 32 Similarly, in a recent study of 33 elite male athletes and matched control subjects, with a median age of 47 years, only 1 athlete had LGE ‘localized subepicardial in the LV posteroinferior region.’ 33 The present study extends these findings by demonstrating a lack of association of focal myocardial necrosis across a significantly older population with longer physical activity histories and encompassing a spectrum of lifelong physical activity histories.…”
Section: Discussionmentioning
confidence: 96%
“…For assessment of the athlete, the presence of LGE with borderline LV wall thickness would strongly suggest pathologic hypertrophy rather than physiologic adaptation. 28,29 CCT is not often used for the assessment of patients with HCM with a few exceptions. In patients with questionable wall thickness measurements by echocardiography and who are unable to tolerate a CMR, CCT could be considered.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%